2013
DOI: 10.1021/es401507k
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Benzalkonium Chloride Disinfectants Results in Change of Microbial Community Structure and Increased Antimicrobial Resistance

Abstract: The effect of benzalkonium chlorides (BACs), a widely used class of quaternary ammonium disinfectants, on microbial community structure and antimicrobial resistance was investigated using three aerobic microbial communities: BACs-unexposed (DP, fed a mixture of dextrin/peptone), BACs-exposed (DPB, fed a mixture of dextrin/peptone and BACs), and BACs-enriched (B, fed only BACs). Long-term exposure to BACs reduced community diversity and resulted in the enrichment of BAC-resistant species, predominantly Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(126 citation statements)
references
References 42 publications
5
118
2
1
Order By: Relevance
“…S5A in the supplemental material). Further study indicated that these efflux pumps confer increased resistance to BACs as well as several antibiotics (7). In the present work, metatranscriptomics revealed significantly increased expression (P Ͻ 0.01 by chisquared test) of these four efflux pump systems at 0.5 h compared to results at 0, 12, and 48 h (see Fig.…”
Section: Fig 2 Genus Contribution To Community Metatranscriptome Durisupporting
confidence: 59%
See 3 more Smart Citations
“…S5A in the supplemental material). Further study indicated that these efflux pumps confer increased resistance to BACs as well as several antibiotics (7). In the present work, metatranscriptomics revealed significantly increased expression (P Ͻ 0.01 by chisquared test) of these four efflux pump systems at 0.5 h compared to results at 0, 12, and 48 h (see Fig.…”
Section: Fig 2 Genus Contribution To Community Metatranscriptome Durisupporting
confidence: 59%
“…Detoxification of BACs or toxic intermediates also is expected to be mediated, at least in part, by the activity of efflux pump systems on a genomic island that was shared by several non-BAC-degrading members of the community (see Fig. S5 in the supplemental material) (7). Community metatranscriptomic data, as well as metabolite analysis of cultures of isolates grown on BACs, indicated that P. nitroreducens strain B cannot metabolize BDMA and, after dealkylation of BACs, appears to generate energy by ␤-oxidation of the alkyl chain and the TCA cycle ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pollution of natural environments with antibiotics and disinfectants affects community structure and leads to increased carriage of resistance genes in environmental organisms (238,239). It is now widely accepted that the natural environment is a recruitment ground for resistant organisms and potential opportunistic pathogens (121,144,213,240).…”
Section: Generation Of New Dna Elements and Newly Resistant Speciesmentioning
confidence: 99%